Perovskite laminated solar cell structure, preparation method and cell

By introducing nickel-doped lead dioxide and tin oxide-potassium bromide composites into perovskite stacked solar cells as interface optimization and modification layers, the perovskite double junction stacked cells are solved in multi-layer interactions. The problem of degradation improves the photoelectric conversion efficiency and stability.

CN119317302APending Publication Date: 2025-01-14江苏先导微电子科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411331635.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing perovskite double junction stacked solar cells may degrade in multi-layer interactions, resulting in limited photoelectric conversion efficiency. How to reasonably design stacked structures to improve efficiency has become a challenge.

Method used

It adopts perovskite stacked solar cell structure, including glass substrate, CIGS layer, window layer, conductive layer, hole transport layer, interface optimization layer, perovskite film layer, interface modification layer, electron transport layer and metal electrode layer. Through the nickel-doped lead dioxide composite and tin-oxidine-potassium bromide-chlorochloride composite as interface optimization and modification layers, electron and hole transport is optimized to reduce carrier composite and interface defects.

Benefits of technology

It improves the photoelectric conversion efficiency and stability of perovskite solar cells, enhances the durability and chemical stability of the cells, optimizes the contact quality between the interface between the perovskite layer and the electron transport layer, and reduces charge loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317302A_ABST
    Figure CN119317302A_ABST
Patent Text Reader

Abstract

The perovskite laminated solar cell comprises a glass substrate, an electrode layer, a CIGS layer, a window layer, a first conductive layer, a hole transport layer, an interface optimization layer, a perovskite film layer, an interface modification layer, a tin dioxide electron transport layer, a second conductive layer and a metal electrode layer which are sequentially laminated. The material of the window layer is cadmium selenide; the interface optimization layer is made of a nickel-doped lead dioxide composite material, and the interface modification layer is made of a tin oxide-bromine chlorine potassium composite material; the first conductive layer and the second conductive layer are made of tungsten-doped indium oxide. According to the invention, the nickel-doped lead dioxide composite layer is arranged as the interface optimization layer, and the tin oxide-bromine chlorine potassium composite layer is arranged as the interface modification layer, so that carrier recombination on the surface of perovskite can be reduced, and the photoelectric conversion efficiency of the cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite stacked solar cell structure, a preparation method and a cell. Background Art

[0002] Solar cells are semiconductor devices that can directly convert sunlight into electrical energy, also known as photovoltaic cells. The working principle of solar cells is mainly based on the photoelectric effect. When sunlight shines on the surface of solar cells, photons are absorbed and excite electrons to form electron-hole pairs. Under the action of the electric field, electrons and holes are separated and move to the two ends of the battery respectively, forming a potential difference, that is, generating electrical energy. Perovskite is also considered to be the most promising low-cost and high-efficiency photovoltaic material for the next generation.

[0003] Organic-inorganic hybrid perovskite solar cells have attracted much attention and developed rapidly internationally due to their outstanding advantages such as low cost, easy preparation and excellent photoelectric performance. The conversion efficiency of single-junction cells has increased from 3.8% in 2009 to more than 15% in 2020. Despite this, there are still some shortcomings in single-junction cells. Single-junction perovskite solar cells mainly absorb sunlight in a specific band and have low efficiency in utilizing sunlight in other bands, which limits their overall photoelectric conversion efficiency. According to research, perovskite double-junction stacked solar cells can achieve higher conversion efficiency than single-layer cells, but existing double-junction stacked solar cells may face more complex challenges because the interaction between the multiple layers may cause degradation, resulting in limited conversion efficiency.

[0004] Therefore, how to rationally design the stacked structure of perovskite solar cells to further improve the photoelectric conversion efficiency of the cells has become a technical problem that technicians in this field need to solve urgently. Summary of the invention

[0005] The present invention provides a perovskite laminated solar cell structure, a preparation method and a battery to solve the problem of how to reasonably design the laminated structure of the perovskite solar cell to improve the photoelectric conversion efficiency of the perovskite solar cell.

[0006] In order to solve the above technical problems, an embodiment of the present invention provides a perovskite stacked solar cell structure, including: a glass substrate, an electrode layer, a CIGS layer, a window layer, a first conductive layer, a hole transport layer, an interface optimization layer, a perovskite film layer, an interface modification layer, a tin dioxide electron transport layer, a second conductive layer and a metal electrode layer;

[0007] The glass substrate is provided on one side of the electrode layer, and the CIGS layer is provided on the other side of the electrode layer;

[0008] The window layer is disposed on a side of the CIGS layer away from the electrode layer, and the first conductive layer is disposed on a side of the window layer away from the CIGS layer;

[0009] The hole transport layer is disposed on a side of the first conductive layer away from the window layer, and the interface optimization layer is disposed on a side of the hole transport layer away from the first conductive layer;

[0010] The perovskite film layer is disposed on a side of the interface optimization layer away from the hole transport layer, and the interface modification layer is disposed on a side of the perovskite film layer away from the interface optimization layer;

[0011] The tin dioxide electron transport layer is provided on a side of the interface modification layer away from the perovskite film layer, and the second conductive layer is provided on a side of the tin dioxide electron transport layer away from the interface modification layer;

[0012] The metal electrode layer is disposed on a side of the second conductive layer away from the tin dioxide electron transport layer;

[0013] Wherein, the material of the window layer is cadmium selenide;

[0014] The material of the interface optimization layer is a nickel-doped lead dioxide composite material, and the material of the interface modification layer is a tin oxide-bromine-potassium chloride composite material;

[0015] The materials of the first conductive layer and the second conductive layer are both tungsten-doped indium oxide.

[0016] Furthermore, the thicknesses of the first conductive layer and the second conductive layer are 30-60 nm and 150-200 nm respectively.

[0017] Furthermore, the hole transport layer is made of nickel oxide with a thickness of 20-30 nm.

[0018] Furthermore, the perovskite film layer is a layer of Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Film layer, thickness is 300-500nm.

[0019] Furthermore, the material of the metal electrode layer is copper, and the thickness is 10-100 nm.

[0020] Another embodiment of the present invention provides a method for preparing a perovskite tandem solar cell, which is applied to the above-mentioned perovskite tandem solar cell structure, comprising:

[0021] Depositing an electrode layer on the glass substrate by magnetron sputtering;

[0022] evaporating a CIGS layer on the electrode layer by a three-step method;

[0023] Vapor depositing a cadmium selenide film on the CIGS layer as a window layer;

[0024] Depositing a tungsten-doped indium oxide layer as a first conductive layer on the window layer by magnetron sputtering;

[0025] Depositing a hole transport layer on the conductive layer by magnetron sputtering;

[0026] Depositing a layer of nickel-doped lead dioxide composite material on the hole transport layer as an interface optimization layer;

[0027] Depositing a perovskite film layer on the interface optimization layer by using a doctor blade coating method;

[0028] Depositing a layer of tin oxide-potassium bromine chloride composite material as an interface modification layer on the perovskite film layer by a slit coating method;

[0029] Depositing an electron transport layer on the interface modification layer by atomic vapor deposition;

[0030] Depositing a tungsten-doped indium oxide layer as a second conductive layer on the electron transport layer by magnetron sputtering;

[0031] A layer of metal electrode is deposited on the second conductive layer by screen printing.

[0032] Furthermore, evaporating a CIGS power generation layer on the electrode layer by a three-step method comprises:

[0033] In the first evaporation process, the temperature of the glass substrate is raised to a first preset temperature threshold to obtain a layer of InGaSe prefabricated film;

[0034] In the second evaporation process, the temperature of the glass substrate is continuously raised to reach a second preset temperature threshold, and a CuInGaSe film layer is evaporated on the InGaSe prefabricated film;

[0035] In the third evaporation process, evaporation is continued on the CuInGaSe film layer to obtain a CIGS power generation layer.

[0036] Furthermore, the step of evaporating a cadmium selenide film on the CIGS layer as a window layer comprises:

[0037] In a vacuum environment, based on a preset evaporation temperature threshold, a cadmium selenide thin film window layer is evaporated on the CIGS layer.

[0038] Furthermore, the preset evaporation temperature threshold is 390-410°C.

[0039] Furthermore, the step of depositing a perovskite film layer on the interface optimization layer by using a scraping method comprises:

[0040] Adding FAI, FABr, CsI, CsBr, PbI2 and PbBr2 in a preset molar ratio to a mixed solution of DMF and DMSO to obtain a precursor solution;

[0041] adding guanidine tetrafluoroborate to the precursor liquid, heating and stirring at a preset temperature and time, and filtering using polytetrafluoroethylene;

[0042] The filtered solution is scraped and coated on the interface optimization layer to obtain the perovskite film layer.

[0043] Another embodiment of the present invention provides a perovskite tandem solar cell, comprising the above-mentioned perovskite tandem solar cell structure.

[0044] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0045] (1) The perovskite CIGS stacked thin-film solar cell of the present invention is provided with a nickel-doped lead dioxide composite layer as an interface optimization layer, which improves the photoelectric conversion efficiency of the cell by improving the isotropic coordination ability of the uncoordinated Pb2+ ion defects on the perovskite surface, optimizing the electron and hole transport, reducing the carrier recombination on the perovskite surface, and optimizing the energy level alignment; and the stability of the nickel-doped lead dioxide composite layer provides additional interface protection for the cell structure, preventing the negative impact of the chemical substances in the NiO layer on the perovskite layer, so as to improve the stability and durability of the solar cell.

[0046] (2) By depositing a layer of tin oxide-potassium bromine chloride composite film between the SnO2 electron transport layer and the perovskite film and using this film as an interface modification layer, the interface between the perovskite layer and the electron transport layer of the solar cell can be optimized, the interface charge recombination can be inhibited, and the charge loss can be reduced; and the interface defects between the SnO2 layer and the perovskite layer can be effectively modified and passivated, thereby reducing electron recombination and increasing the efficiency of the solar cell; and due to the chemical stability of tin oxide-potassium bromine chloride, it can resist the negative impact of environmental factors, thereby protecting the perovskite layer from potential chemical reactions and improving the stability and durability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic structural diagram of a perovskite tandem solar cell provided by the present invention;

[0048] Figure 2 is a schematic structural diagram of a perovskite tandem solar cell in one embodiment of the present invention;

[0049] Reference numerals:

[0050] 1 glass substrate, 2 electrode layer, 3 CIGS layer, 4 window layer, 5 first conductive layer, 6 hole transport layer, 7 interface optimization layer, 8 perovskite film layer, 9 interface modification layer, 10 tin dioxide electron transport layer, 11 second conductive layer and 12 metal electrode layer. DETAILED DESCRIPTION

[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] In the description of this application, the terms "first", "second", "third", etc. are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", "third", etc. may explicitly or implicitly include one or more of the feature. In the description of this application, unless otherwise specified, "plurality" means two or more.

[0053] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be a connection between the two elements. The terms "vertical", "horizontal", "left", "right", "upper", "lower" and similar expressions used herein are only for illustrative purposes, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0054] In the description of this application, it should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood by specific circumstances.

[0055] Double-junction (tandem) perovskite solar cells are stacked by two or more perovskite layers with different band gaps, or perovskite layers are stacked with other types of solar cells (such as crystalline silicon solar cells) to form a "tandem" cell that can absorb a wider solar spectrum. This type of cell absorbs sunlight with a wider range of wavelengths through differential absorption, reducing light and heat losses, thereby improving cell conversion efficiency. At present, the efficiency of perovskite tandem cells has exceeded 30%, and there is still much room for improvement.

[0056] An embodiment of the present invention provides a perovskite tandem solar cell. For details, see Figure 1 , Figure 1 A schematic structural diagram of a perovskite tandem solar cell provided by the present invention is shown, comprising:

[0057] Glass substrate 1, electrode layer 2, CIGS layer 3, window layer 4, first conductive layer 5, hole transport layer 6, interface optimization layer 7, perovskite film layer 8, interface modification layer 9, tin dioxide electron transport layer 10, second conductive layer 11 and metal electrode layer 12. Specifically, from Figure 1 It can be seen that:

[0058] The glass substrate is disposed on one side of the electrode layer, and the CIGS layer is disposed on the other side of the electrode layer.

[0059] In perovskite tandem solar cells, the glass substrate usually serves as the supporting structure of the entire cell, and its surface is specially treated (such as coating) to form a transparent conductive layer that can collect and transmit photogenerated charges. In some embodiments, FTO (fluorine-doped tin oxide) conductive glass is selected as the substrate material. FTO conductive glass has excellent visible light transmittance and low resistivity, which can reduce the capacity loss of the cell and improve the photoelectric conversion efficiency.

[0060] In some embodiments, Mo (molybdenum) may be selected as the electrode layer. Preferably, the thickness of the Mo layer may be 20-40 nm.

[0061] It can be understood that in the embodiment of the present invention, the CIGS (copper indium gallium selenide) layer is used as the power generation layer, and the band gap width of the CIGS solar cell can be adjusted in a large range (usually between 1.02eV and 1.67eV), which makes it very suitable as the bottom cell power generation layer of the stacked cell. Preferably, the CIGS film layer thickness is 1.5-2.5um.

[0062] The window layer is disposed on a side of the CIGS layer away from the electrode layer, and the first conductive layer is disposed on a side of the window layer away from the CIGS layer.

[0063] It is understandable that the window layer is a key layer above the CIGS layer, and its material needs to have good light transmittance, conductivity and good contact with the CIGS layer. Cadmium selenide (CdSe), as a semiconductor material, has a wide bandgap and high light transmittance. In addition, cadmium selenide can form good contact with the CIGS layer, which helps to reduce the interface resistance and improve the fill factor and open circuit voltage of the battery. Therefore, in some embodiments, the material of the window layer is cadmium selenide, and preferably, the thickness of the CdSe layer can be 40-60nm.

[0064] In some embodiments, the material of the first conductive layer is tungsten-doped indium oxide (In2O3: W, IWO), which is a transparent conductive oxide with high transmittance and low resistivity. The IWO layer can effectively collect the photogenerated electrons transmitted from the window layer and export them to the external circuit. It can also prevent the window layer from being corroded and damaged by the external environment, thereby extending the service life of the battery. It can be understood that by optimizing the thickness, doping concentration and other parameters of the IWO layer, the photoelectric conversion efficiency and stability of the battery can be further improved. Preferably, the thickness of the first conductive layer can be 30-60nm.

[0065] The hole transport layer is disposed on a side of the first conductive layer away from the window layer, and the interface optimization layer is disposed on a side of the hole transport layer away from the first conductive layer.

[0066] In some embodiments, the material of the hole transport layer is nickel oxide (NiO) with a thickness of 20-30 nm. NiO is a p-type semiconductor with excellent hole transport capability. It can effectively collect and transport holes from the perovskite layer or CIGS layer, reducing the recombination loss of holes during the transport process.

[0067] It is understandable that setting an interface optimization layer can fill the tiny gaps between adjacent layers, reduce interface defects, and thus improve the contact quality between layers. In addition, in solar cells, the interface is one of the main places for photogenerated carrier recombination. The interface optimization layer can inhibit the carrier recombination process at the interface through its special physical and chemical properties, which helps to improve the collection efficiency of photogenerated carriers and increase the open circuit voltage and short circuit current density of the battery.

[0068] In some embodiments of the present invention, the material of the interface optimization layer can be selected as a nickel-doped lead dioxide composite material (Ni-PbO2), and the thickness of the Ni-PbO2 layer can be 10-15nm. The Ni-PbO2 layer is used as an interface optimization layer to improve the isotropic coordination ability of the uncoordinated Pb2+ ion defects on the surface of the perovskite, reduce the recombination of carriers on the surface of the perovskite and improve the PCE value. It can be understood that Ni-PbO2 is a composite material composed of (nickel) Ni doped with (lead dioxide) PbO2.

[0069] The introduction of the Ni-PbO2 layer can improve the energy level alignment between the perovskite layer and the hole transport layer (such as NiO). The PbO2 layer itself has a certain band structure. By adjusting its composition and deposition conditions, the energy level alignment can be optimized, thereby reducing the recombination of electrons and holes and improving the photoelectric conversion efficiency.

[0070] It is understandable that Ni-PbO2 combines the advantages of NiO and PbO2 to a certain extent. NiO, as a hole transport material, has good hole transport ability, while PbO2 can improve electron transport performance. Therefore, the Ni-PbO2 layer can optimize the transmission of electrons and holes at the interface, which can form a more uniform electric field and facilitate the effective migration of carriers. This process enhances the carrier concentration of the perovskite layer and improves the photoelectric conversion efficiency.

[0071] It is understandable that since PbO2 is a lead oxide with a higher oxidation state, the Ni-PbO2 layer can enhance the interface stability and prevent the negative impact of the chemical substances in the NiO layer on the perovskite layer, thereby improving the long-term stability and durability of the solar cell. The perovskite film layer is provided on the side of the interface optimization layer away from the hole transport layer, and the interface modification layer is provided on the side of the perovskite film layer away from the interface optimization layer.

[0072] In some embodiments of the present invention, the perovskite film layer is a layer of Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The film layer reacts with sunlight to generate electrons and holes. Preferably, the thickness of the film layer is 300-500nm.

[0073] The material of the interface modification layer is a tin oxide-bromine-chlorine-potassium composite material (SnO2-K2ClBr). In the embodiment of the present invention, the tin oxide-bromine-chlorine-potassium composite material refers to SnO2-K2ClBr, which is a mixture of tin dioxide and a compound containing bromine, chlorine and potassium. The interface modification layer can optimize the interface between the perovskite layer and the electron transport layer, inhibit interfacial charge recombination, reduce charge loss and increase efficiency. In some embodiments of the present invention, preferably, the thickness of the interface modification layer is 10-15nm.

[0074] It is understandable that the doping of bromine-chlorine-potassium composite material (K2ClBr) can change the electronic structure of tin dioxide to adjust its energy band structure, thereby optimizing the injection and transmission path of electrons. Therefore, SnO2-K2ClBr can adjust the energy level alignment between the SnO2 layer and the perovskite layer. Good energy level alignment helps reduce the energy loss of the battery and improve the open circuit voltage and conversion efficiency of the battery.

[0075] The SnO2-K2ClBr layer is arranged between the perovskite layer and the electron transport layer, which can effectively modify and passivate the interface defects between the two layers. It can be understood that the doping of K2ClBr makes the SnO2 layer have better chemical stability, which can resist the negative effects of environmental factors (such as humidity and oxidation), thereby improving the overall performance of the battery. The tin dioxide electron transport layer is arranged on the side of the interface modification layer away from the perovskite film layer, and the second conductive layer is arranged on the side of the tin dioxide electron transport layer away from the interface modification layer.

[0076] In some embodiments of the present invention, the material of the electron transport layer can be tin dioxide (SnO2), preferably, its thickness can be 10-15nm. The electron transport layer is used to transmit electrons generated by the perovskite photovoltaic reaction, and SnO2 has high transmittance, low resistivity and good chemical stability, which can greatly improve the photoelectric conversion efficiency, stability and service life of the battery.

[0077] Preferably, in some embodiments of the present invention, the material of the second conductive layer is tungsten-doped indium oxide, and the thickness thereof can be set to 150-200 nm.

[0078] The metal electrode layer is disposed on a side of the second conductive layer away from the tin dioxide electron transport layer.

[0079] In some embodiments of the present invention, preferably, the material of the metal electrode is copper (Cu) and the thickness thereof is 10-100 nm.

[0080] In summary, the present invention improves the stacked structure of the perovskite solar cell, deposits a Ni-PbO2 layer on the hole transport layer by magnetron sputtering as an interface optimization layer to enhance the isotropic coordination ability of the uncoordinated Pb2+ ion defects on the perovskite surface, thereby reducing the recombination of carriers on the perovskite surface and improving the photoelectric conversion efficiency of the battery; and deposits a SnO2 layer between the SnO2 electron transport layer and the perovskite film layer. 2- The K2ClBr film layer is used as an interface modification layer, which can optimize the interface between the perovskite layer and the electron transport layer, inhibit interface charge recombination, reduce charge loss, and increase the photoelectric conversion efficiency of solar cells.

[0081] An embodiment of the present invention provides a method for preparing a perovskite tandem solar cell, specifically comprising the following steps:

[0082] S1. Depositing an electrode layer on the glass substrate by magnetron sputtering. It is understood that the magnetron sputtering equipment includes a vacuum system, a sputtering power supply, a target rack, a substrate rack and other parts. Then a gas supply system is required to provide a corresponding inert gas (such as argon Ar) as a sputtering atmosphere to maintain the vacuum degree during the sputtering process and prevent the target material from oxidizing. In some embodiments of the present invention, the conductive glass substrate can be cleaned to remove impurities such as grease and dust on the surface. Optional steps include but are not limited to using ultrasonic cleaning, acid cleaning and other methods to improve the cleanliness and activity of the substrate surface.

[0083] S2. Evaporating a CIGS layer on the electrode layer by a three-step method.

[0084] S3, vapor-depositing a cadmium selenide film on the CIGS layer as a window layer.

[0085] S4, depositing a tungsten-doped indium oxide layer as the first conductive layer on the window layer by magnetron sputtering. It is worth noting that in some embodiments of the present invention, the thickness, doping concentration and other parameters of the IWO layer can be optimized to further improve the photoelectric conversion efficiency and stability of the battery.

[0086] S5. Depositing a hole transport layer on the conductive layer by magnetron sputtering.

[0087] S6, depositing a layer of nickel-doped lead dioxide composite material on the hole transport layer as an interface optimization layer. It can be understood that the Ni-PbO2 layer can form a flat film with strong adhesion during the deposition process, which can improve the interface quality between the hole transport layer and the perovskite layer, making the film structure uniform and continuous. S7, depositing a perovskite film layer on the interface optimization layer by a scraping method.

[0088] S8. Depositing a layer of tin oxide-potassium bromine chloride composite material as an interface modification layer on the perovskite film layer by a slit coating method.

[0089] Among them, it can be understood that slot-die coating is a high-precision, high-speed thin-film coating technology, which is widely used in photovoltaics, displays, electronics and other fields. It uses a slit nozzle with precise width and shape to evenly and continuously coat the liquid material on the substrate. Therefore, the interface modification layer has good flatness and adhesion through the slit coating method and the doping of bromine-chlorine-potassium composite material, thereby improving the deposition quality and promoting the interface uniformity between the electron transport layer and the perovskite layer.

[0090] S9. Depositing an electron transport layer on the interface modification layer by atomic vapor deposition.

[0091] S10, depositing a tungsten-doped indium oxide layer as a second conductive layer on the electron transport layer by magnetron sputtering.

[0092] S11. Depositing a layer of metal electrode on the second conductive layer by screen printing.

[0093] According to a specific embodiment of the preparation method of the present invention, in the preparation process of step S2, the CIGS film is evaporated on the substrate in three steps, specifically:

[0094] In the first evaporation process, the temperature of the glass substrate is raised to a first preset temperature threshold to obtain a layer of InGaSe prefabricated film. The formation of the prefabricated film is the basis for the copper element to be correctly incorporated in the subsequent steps to form a CIGS structure.

[0095] The substrate temperature is set between 300-400°C, that is, the first preset temperature threshold refers to the substrate temperature set during the first step of evaporation. In this step, the main elements In (indium), Ga (gallium) and Se (selenium) are evaporated. These elements co-evaporate and react on the substrate to form an InGaSe prefilm. The formation of the prefilm also helps to reduce defects and phase separation, and improve the quality of the CIGS film.

[0096] In the second evaporation process, the temperature of the glass substrate is further increased to reach a second preset temperature threshold, and a CuInGaSe film layer is evaporated on the InGaSe prefabricated film. Specifically:

[0097] The substrate temperature is raised to 550-580°C, that is, the second preset temperature threshold refers to the temperature value to which the substrate temperature is raised during the second evaporation step, and Cu is evaporated in a Se atmosphere to form a Cu-rich CuInGaSe film layer. The formation of the Cu-rich layer helps to optimize the band gap and optoelectronic properties of the CIGS film by adjusting the element ratio in subsequent steps.

[0098] In the third evaporation process, evaporation is continued on the CuInGaSe film layer to obtain a CIGS power generation layer. The purpose of this step is to evaporate the remaining In, Ga, and Se and eliminate the Cu2Se phase, so that a CIGS thin film is obtained. Since the presence of the Cu2Se phase will reduce the photoelectric conversion efficiency of the CIGS film, eliminating the Cu2Se phase can ensure that the CIGS film has good photoelectric performance.

[0099] According to a specific embodiment of the preparation method of the present invention, in the preparation process of step S3, a cadmium selenide thin film window layer is evaporated on the CIGS layer in a vacuum environment based on a preset evaporation temperature threshold. The preset evaporation temperature threshold is 390-410°C.

[0100] During this process, it is necessary to ensure that the vacuum environment has been established and maintained at an appropriate level to avoid the introduction of impurities or gases during the evaporation process. According to the preset evaporation temperature threshold, prepare the evaporation source (usually CdSe material) and the heating device. It is understandable that during the evaporation process, other parameters need to be controlled, such as evaporation rate, evaporation time, substrate film layer temperature (here refers to the temperature of the CIGS layer) and the distance between the substrate film layer and the evaporation source, etc. These parameters jointly determine the final quality of the CdSe film.

[0101] According to a specific embodiment of the preparation method of the present invention, in step S7, a layer of Cs is deposited by a scraping method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Perovskite film layer, specifically:

[0102] FAI, FABr, CsI, CsBr, PbI2 and PbBr2 in a preset molar ratio are added to a mixed solution of DMF and DMSO to obtain a precursor solution.

[0103] Among them, DMF (N, N-dimethylformamide, chemical formula is C3H7NO) and DMSO (dimethyl sulfoxide, chemical formula is C2H6OS), preferably, a mixed solution of DMF and DMSO with a volume ratio of 4:1 can be prepared.

[0104] The six compounds FAI (formamidine hydroiodic acid, chemical formula CH5IN2), FABr (formamidine hydrobromic acid, chemical formula CH5BrN2), CsI (cesium iodide), CsBr (cesium bromide), PbI2 (lead iodide) and PbBr2 (lead bromide) are added to the above-mentioned mixed solution according to a preset molar ratio. Preferably, the preset molar ratio can be 0.48:0.32:0.12:0.08:0.6:0.4.

[0105] Guanidine tetrafluoroborate (GuaBF4) is added to the precursor liquid, heated and stirred at a preset temperature and time, and filtered using polytetrafluoroethylene. Specifically:

[0106] Guanidine tetrafluoroborate is also added to the mixed solution. Guanidine tetrafluoroborate can be used as an additive or stabilizer to improve the performance or stability of the final product. Then, the obtained mixed solution is heated and stirred at a preset temperature. The purpose of this step is to promote sufficient reaction and mixing between the components in the solution, as well as possible dissolution or improvement of solubility. Heating and stirring both help to accelerate the reaction rate and improve the reaction efficiency. Preferably, the preset temperature can be 50°C and the stirring time can be 2 hours.

[0107] Preferably, the mixed solution is filtered using a polytetrafluoroethylene (PTFE) filter. The PTFE filter has good chemical stability and corrosion resistance. The purpose of this step is to remove insoluble impurities or particles in the solution to obtain a purer solution.

[0108] Finally, the filtered solution is scraped onto the interface optimization layer to obtain the perovskite film layer.

[0109] In some embodiments of the preparation method described in the present invention, in the preparation process of step S9, in order to further optimize the interface between the perovskite layer and the electron transport layer to suppress the interface charge recombination, a vapor deposition method is used to deposit the electron transport layer. It can be understood that the atomic layer deposition method is a thin film deposition technology based on surface chemical reactions. It grows the desired film layer by layer by alternately passing a precursor (usually a gaseous or vapor compound) into the reaction chamber and chemically adsorbing and reacting on the surface of the substrate. Since only one layer of atoms or molecules is deposited at a time, the thickness and composition of the film can be precisely controlled. Specifically, it may include at least the following implementation steps:

[0110] First, ensure that the interface modification layer (SnO2-K2ClBr) has been uniformly and stably deposited on the perovskite film layer, and that the surface is clean and free of contaminants.

[0111] Set up the reaction chamber: Place the substrate into the atomic vapor deposition reaction chamber and adjust the reaction chamber parameters such as temperature, pressure, and gas flow to suit the deposition conditions of the selected electron transport material.

[0112] Alternating the introduction of precursors: According to the chemical properties of the selected electron transport material, appropriate precursors are selected and introduced into the reaction chamber alternately. After each introduction of the precursor, there is a short waiting time to allow the precursor to chemically adsorb on the substrate surface. Then, an inert gas (such as nitrogen or argon) can be introduced for purging to remove unreacted precursors and byproducts.

[0113] Repeat the deposition process: By repeating the above steps, the desired electron transport layer can be grown layer by layer. Since only one layer of atoms or molecules is deposited each time, the thickness of the film can be precisely controlled by controlling the number of deposition cycles.

[0114] In order to further clearly reflect the structural characteristics of the perovskite tandem solar cell of the present invention, a perovskite tandem solar cell and a preparation method thereof provided by the present invention are described in detail below in combination with specific embodiments.

[0115] The reagents used in the following examples are all commercially available.

[0116] Example 1

[0117] (1) A Mo electrode layer was deposited on the FTO conductive glass using a magnetron sputtering method, and the Mo layer thickness was 30 nm.

[0118] (2) Evaporating the CIGS power generation layer on the Mo electrode layer in three steps:

[0119] The first step: when the substrate temperature is 300-400℃, about 90% of In, Ga, and Se are co-evaporated to form an InGaSe prefabricated film; the second step: when the substrate temperature is increased to 550-580℃, Cu is evaporated in a Se atmosphere to form a Cu-rich CuInGaSe film layer; the third step: the remaining 10% of In, Ga, and Se are evaporated, and the Cu2Se phase is eliminated. The thickness of the prepared CIGS film layer is 2um.

[0120] (3) Under vacuum conditions, at a temperature of 400° C., a CdSe layer is prepared by evaporation. The thickness of the CdSe layer is 50 nm.

[0121] (4) A tungsten-doped indium oxide (In2O3: W, IWO) layer is deposited on the CdSe layer by a magnetron sputtering method. The thickness of the IWO layer is 45 nm.

[0122] (5) A NiO layer is deposited by magnetron sputtering, and the thickness of the NiO layer is 25 nm.

[0123] (6) A Ni-PbO2 layer is deposited on the NiO layer by magnetron sputtering as an interface optimization layer. The thickness of the Ni-PbO2 layer is 13 nm.

[0124] (7) Deposit a layer of Cs on the interface optimization layer by scraping 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Perovskite film layer, the film thickness is 400nm. Specifically including:

[0125] 7.1 Preparation of perovskite solution:

[0126] The precursor solution was prepared in DMF and DMSO at a volume ratio of 4:1.

[0127] A mixture of FAI, FABr, CsI, CsBr, PbI2 and PbBr2 with a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 was prepared and added to the above-mentioned mixture of DMF and DMSO to prepare a precursor solution.

[0128] Guanidine tetrafluoroborate was added to the precursor solution, and the precursor solution was heated and stirred at 50° C. for 2 hours, and then filtered with 0.22 um PTFE.

[0129] 7.2 Preparation of perovskite film:

[0130] The filtered solution was scraped onto the Ni-PbO2 film layer, and the obtained film layer had a thickness of 400 nm.

[0131] (8) A SnO2-K2ClBr film layer is deposited on the perovskite film layer by slit coating as an interface modification layer with a thickness of 13 nm.

[0132] (9) A SnO2 layer with a thickness of 15 nm is deposited on the interface modification layer using an atomic vapor deposition method.

[0133] (10) A layer of IWO is deposited on the SnO2 layer by magnetron sputtering. The thickness of the IWO layer is 150 nm.

[0134] (11) A Cu layer is deposited on the IWO layer by screen printing as an electrode. The thickness of the Cu layer is 50 nm.

[0135] A solar cell is prepared according to the method for preparing a perovskite solar tandem cell in Embodiment 1. For details, see Figure 2 , Figure 2A schematic structural diagram of a perovskite tandem solar cell in one of the embodiments is shown, and the photoelectric conversion efficiency of the perovskite solar tandem cell prepared in Implementation 1 is tested.

[0136] Example 2

[0137] A perovskite tandem solar cell was prepared according to the method of Example 1, except that:

[0138] (6) The thickness of the Ni-PbO2 interface optimization layer can be set to 5 nm, 10 nm, 15 nm and 20 nm, and the thickness of the other film layers is the same. The SnO2-K2ClBr interface modification layer with a thickness of 13 nm is used as a comparative reference example to observe the effect of interface optimization layers of different thicknesses on the photoelectric conversion efficiency of the battery.

[0139] Example 3

[0140] A perovskite tandem solar cell was prepared according to the method of Example 1, except that:

[0141] (8) A SnO2-K2ClBr film layer was deposited on the perovskite film layer by slit coating as an interface modification layer with thicknesses of 5 nm, 10 nm, 15 nm and 20 nm. Similarly, a Ni-PbO2 interface optimization layer with a thickness of 13 nm was used as a comparative reference example to observe the effects of interface modification layers of different thicknesses on the photoelectric conversion efficiency of the battery.

[0142] Based on the preparation, observation and testing process of Example 1, Example 2 and Example 3, each example and comparison are shown in Table 1:

[0143] Table 1 Effects of different interface optimization layer and interface modification layer thickness on solar cell performance

[0144]

[0145]

[0146] It can be seen from the results in Table 1 that, compared with Examples 2 and 3, the perovskite solar cell prepared by Example 1 of the present invention is superior to Examples 2 and 3 in terms of photoelectric conversion efficiency. That is to say, the thicker the Ni-PbO2 interface optimization layer and the SnO2-K2ClBr interface modification layer, the higher the conversion performance. The perovskite solar cell prepared by using a 13nm Ni-PbO2 interface optimization layer and a SnO2-K2ClBr interface modification layer can more effectively reduce carrier recombination and obtain higher photoelectric conversion efficiency.

[0147] Another embodiment of the present invention provides a perovskite tandem solar cell, comprising the above-mentioned perovskite tandem solar cell structure. The perovskite tandem solar cell of the present invention is provided with an interface modification layer and an interface optimization layer on the upper and lower sides of the perovskite film layer to optimize the overall performance of the cell, which can effectively improve the conversion efficiency of the cell compared with the traditional tandem cell.

[0148] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A perovskite tandem solar cell structure, characterized in that: It includes a glass substrate, an electrode layer, a CIGS layer, a window layer, a first conductive layer, a hole transport layer, an interface optimization layer, a perovskite film layer, an interface modification layer, a tin dioxide electron transport layer, a second conductive layer and a metal electrode layer; The glass substrate is provided on one side of the electrode layer, and the CIGS layer is provided on the other side of the electrode layer; The window layer is disposed on a side of the CIGS layer away from the electrode layer, and the first conductive layer is disposed on a side of the window layer away from the CIGS layer; The hole transport layer is disposed on a side of the first conductive layer away from the window layer, and the interface optimization layer is disposed on a side of the hole transport layer away from the first conductive layer; The perovskite film layer is disposed on a side of the interface optimization layer away from the hole transport layer, and the interface modification layer is disposed on a side of the perovskite film layer away from the interface optimization layer; The tin dioxide electron transport layer is provided on a side of the interface modification layer away from the perovskite film layer, and the second conductive layer is provided on a side of the tin dioxide electron transport layer away from the interface modification layer; The metal electrode layer is disposed on a side of the second conductive layer away from the tin dioxide electron transport layer; Wherein, the material of the window layer is cadmium selenide; The material of the interface optimization layer is a nickel-doped lead dioxide composite material, and the material of the interface modification layer is a tin oxide-bromine-potassium chloride composite material; The materials of the first conductive layer and the second conductive layer are both tungsten-doped indium oxide.

2. The perovskite tandem solar cell structure according to claim 1, characterized in that: The thicknesses of the first conductive layer and the second conductive layer are 30-60 nm and 150-200 nm respectively.

3. The perovskite tandem solar cell structure according to claim 1, characterized in that: The hole transport layer is made of nickel oxide and has a thickness of 20-30 nm.

4. The perovskite tandem solar cell structure according to claim 1, characterized in that: The perovskite film layer is a layer of Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Film layer, thickness is 300-500nm.

5. A method for preparing a perovskite tandem solar cell, applied to the perovskite tandem solar cell structure according to any one of claims 1 to 4, characterized in that: The method comprises: Depositing an electrode layer on the glass substrate by magnetron sputtering; evaporating a CIGS layer on the electrode layer by a three-step method; Vapor depositing a cadmium selenide film on the CIGS layer as a window layer; Depositing a tungsten-doped indium oxide layer as a first conductive layer on the window layer by magnetron sputtering; Depositing a hole transport layer on the conductive layer by magnetron sputtering; Depositing a layer of nickel-doped lead dioxide composite material on the hole transport layer as an interface optimization layer; Depositing a perovskite film layer on the interface optimization layer by using a doctor blade coating method; Depositing a layer of tin oxide-potassium bromine chloride composite material as an interface modification layer on the perovskite film layer by a slit coating method; Depositing an electron transport layer on the interface modification layer by atomic vapor deposition; Depositing a tungsten-doped indium oxide layer as a second conductive layer on the electron transport layer by magnetron sputtering; A layer of metal electrode is deposited on the second conductive layer by screen printing.

6. The method for preparing a perovskite tandem solar cell according to claim 5, characterized in that: The step of evaporating a CIGS power generation layer on the electrode layer by a three-step method comprises: In the first evaporation process, the temperature of the glass substrate is raised to a first preset temperature threshold to obtain a layer of InGaSe prefabricated film; In the second evaporation process, the temperature of the glass substrate is continuously raised to reach a second preset temperature threshold, and a CuInGaSe film layer is evaporated on the InGaSe prefabricated film; In the third evaporation process, evaporation is continued on the CuInGaSe film layer to obtain a CIGS power generation layer.

7. The method for preparing a perovskite tandem solar cell according to claim 5, characterized in that: The step of evaporating a cadmium selenide film on the CIGS layer as a window layer comprises: In a vacuum environment, based on a preset evaporation temperature threshold, a cadmium selenide thin film window layer is evaporated on the CIGS layer.

8. The method for preparing a perovskite tandem solar cell according to claim 7, characterized in that: The preset evaporation temperature threshold is 390-410°C.

9. The method for preparing a perovskite tandem solar cell according to claim 5, characterized in that: The method of depositing a perovskite film layer on the interface optimization layer by using a scraping method comprises: Adding FAI, FABr, CsI, CsBr, PbI2 and PbBr2 in a preset molar ratio to a mixed solution of DMF and DMSO to obtain a precursor solution; adding guanidine tetrafluoroborate to the precursor liquid, heating and stirring at a preset temperature and time, and filtering using polytetrafluoroethylene; The filtered solution is scraped and coated on the interface optimization layer to obtain the perovskite film layer.

10. A perovskite tandem solar cell, characterized in that: It comprises the perovskite tandem solar cell structure as described in any one of claims 1 to 4.